Dysregulation of the TNF-Α/IL-10 Axis and Microrna-146a Expression in Patients with Newly Diagnosed Graves ‘disease - gawwam, Ameer ali kadhim al. (Journal of Science in Medicine and Life, 2025)
Background: The Graves' disease (GD) manifests as an autoimmune disturbance characterized by hyperthyroidism advertised by the presence of autoantibodies against the thyrotropin receptor. The imbalance of cytokines, mainly between pro-inflammatory TNF-α and anti-inflammatory IL-10, is of great importance in this disease's pathogenesis. MicroRNA-146a (miRNA-146a) is a key regulator of innate immunity, but it is unclear what role it plays in modulating such cytokine balance in GD. Aim: The goal of this study was to check the latest TNF-α, IL-10, and miRNA-146a levels in patients with GD, and to correlate their values with clinical hyperthyroid status. Methods: Forty-five newly diagnosed, untreated GD patients and 30 healthy controls who were matched for age and sex. The enzyme-linked immunosorbent assay (ELISA) was used to measure the levels of TNF-α and IL-10 in the serum. Quantitative real-time polymerase chain reaction (RT-PCR) was used to find out how much miRNA-146a was expressed in peripheral blood. Results: The TNF-α/IL-10 ratio was significantly higher in GD patients due to significantly higher blood levels of TNF-α and significantly lower levels of IL-10 as compared to controls. In GD patients, the expression of miRNA-146a was significantly elevated. There was a significant positive connection found between serum TNF-α levels and miRNA-146a expression. In contrast, there was a negative correlation between serum IL-10 levels and miRNA-146a expression. Additionally, there were positive relationships between blood free triiodothyronine (FT3) and thyrotropin receptor antibodies (TRAbs) and both miRNA-146a and TNF-α levels Conclusion: The results show that miRNA-146a overexpression is linked to a pro-inflammatory state in GD, which is typified by increased TNF-α and decreased IL-10. In Graves' disease, miRNA-146a might be a new biomarker and a possible target for treatment that modifies the immune system.